Chemoenzymatic Synthesis of Fluorinated Cellodextrins Identifies a New Allomorph for Cellulose‐Like Materials. Issue 4 (9th December 2020) - de Andrade, Peterson; Muñoz‐García, Juan C.; Pergolizzi, Giulia; Gabrielli, Valeria; Nepogodiev, Sergey A.; Iuga, Dinu; Fábián, László; Nigmatullin, Rinat; Johns, Marcus A.; Harniman, Robert; Eichhorn, Stephen J.; Angulo, Jesús; et al.
Abstract: Understanding the fine details of the self‐assembly of building blocks into complex hierarchical structures represents a major challenge en route to the design and preparation of soft‐matter materials with specific properties. Enzymatically synthesised cellodextrins are known to have limited water solubility beyond DP9, a point at which they self‐assemble into particles resembling the antiparallel cellulose II crystalline packing. We have prepared and characterised a series of site‐selectively fluorinated cellodextrins with different degrees of fluorination and substitution patterns by chemoenzymatic synthesis. Bearing in mind the potential disruption of the hydrogen‐bond network of cellulose II, we have prepared and characterised a multiply 6‐fluorinated cellodextrin. In addition, a series of single site‐selectively fluorinated cellodextrins was synthesised to assess the structural impact upon the addition of one fluorine atom per chain. The structural characterisation of these materials at different length scales, combining advanced NMR spectroscopy and microscopy methods, showed that a 6‐fluorinated donor substrate yielded multiply 6‐fluorinated cellodextrin chains that assembled into particles presenting morphological and crystallinity features, and intermolecular interactions, that are unprecedented for cellulose‐like materials. Abstract : Generating glycomaterials : Enzymatic incorporation of singly and multiply fluorinated glucose residues into cellodextrin chains produces selectively fluorinated cellodextrins that self‐assemble into crystalline materials. Multiply 6‐fluorinated cellodextrin gave rise to an allomorph not previously reported for celluloses or cellulose‐like materials. Our findings highlight the potential of chemoenzymatic synthesis for generating novel glycomaterials of controlled molecular structure and morphology.